(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is devoted to the description of paremias as an exponent of folk wisdom and carriers of national color. Paremias are special units of language, interesting as a means of understanding the national character of a people. They are understandable and accessible to different nations, as they are based on typical life situations, reflect the logical thinking of the people.